Comparative genetic diversity and antimicrobial susceptibility patterns of escherichia coli from selected animals and environmental sources in Sarawak, Malaysia - Chong, Yee Ling (Universiti Malaysia Sarawak (UNIMAS), 2007)
A total of 312 Escherichia coli isolates were recovered from broiler and vi llage chickens, bats, rodents, and swine sewage effluents, in Sarawak, based on their biochemical tests and morphological characteristics. A comparison of the Enterobacteriaceae species revealed that enteric bacteria and E. coli are common members of microflora in all the environmental samples tested except for bat samples. The total recovery rate of E. coli was only 5.5% from a total of 239 bat samples. More than 70% of the total isolates were detected as typical E. coli (sorbitol fermenter and possess GUD activity). Detection of sIx I, stx2, rfbE and jliC"7 genes using multiplex PCR method revealed that none of the 130 representative E. coli isolates was confirmed as STEC or E. coli OI57:H7. The absence of pathogenic genes indicates that these animals and environmental sources are not important reservoirs of STEC or E. coli 0157:H7 in Sarawak. The antimicrobial susceptibility characteristics of 172 E. coli isolates for antibiotic agents commonly used in the animal husbandry industry in Sarawak was studied. In general, the most frequently encountered form of resistance in all samples was resistance to tetracycline (43.6%) and sulphamethoxazole-trimethoprim (25.58%). The multiple-antibiotic-resistance (MAR) indices were highest for broiler chicken isolates (0.479) and lowest for bat isolates (0.013). All isolates from both broiler chicken and swine sewage effluent samples were multidrug-resistant E. coli. High MAR indices as well as prevalence of multiple-resistance patterns of isolates trom broiler chickens and swine sewage effluents raise a concern on the dissemination of these bacteria to human via food-consumption. The E. coli isolates from wildlife had an average MAR index of only 0.172. Thus, wildlife does not present a high risk of spreading antibiotic-resistant E. coli to the environments. A total of 58 representative E. coli isolates were assessed to study the genetic profiles of these bacteria using PFGE, RAPD-PCR, and ERIC-PCR genotyping methods. Among these methods, only RAPD-PCR generated dendrogram successfully grouped the E. coli isolates into their respective animal sample sources and clearly differentiate between food animal sources and wildlife sources. This study also provided the first approach to combine three different molecular subtyping methods in a single dendrogram for differentiating the animal sources of E. coli isolates. Dendrograms generated from RAPD-PCR and combined-RAPD-ERIC-PFGE fingerprinting patterns demonstrated that E. coli isolates sampled from environmental sources in Sarawak were non-randomly distributed but specific to an animal host which accounted for the genetic variation in the E. coli populations. Further study to trace any changes that may occurred in the genetic composition of the isolates during the transition from the chickens' hosts to the external environments was done using 38 representative E. coli isolates from chicken samples. As village chickens were regarded as the samples from natural habitat, this study revealed that clonal relationships occurred between the E. coli isolates from two different habitats of village chicken samples. Broiler chickens were considered as control sample sources. Based on the genetic profiles, some changes in the genetic materials had occurred during the transition of the E. coli isolates from the broiler chickens to the external environments. This findings based on the fingerprinting profiles through genotyping methods would aid in the future study on the genetic diversity and epidemiological investigations of this bacterium.